2019
DOI: 10.1177/1539449219844749
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzing Research to Optimize Cancer Survivors’ Participation in Work and Life Roles

Abstract: Participation refers to a state of health in which a person is able to fully engage in roles and life situations. Adults living with and beyond cancer often report persistent participation restrictions that affect their productivity and quality of life. The American Occupational Therapy Foundation convened a group of scientists from seven different disciplines in a Planning Grant Collective (PGC) to stimulate research to identify scalable ways to preserve and optimize participation among cancer survivors. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…generalize to resumption of roles and routines in daily life. The evidence suggests that changes in impairmentbased concerns do not generalize to changes in participation (Newman et al, 2019b). Of the small portion of the study sample that received cancer rehabilitation services, referrals were only linked to impairment-related concerns of mobility, lymphedema management, debility, and swallowing.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…generalize to resumption of roles and routines in daily life. The evidence suggests that changes in impairmentbased concerns do not generalize to changes in participation (Newman et al, 2019b). Of the small portion of the study sample that received cancer rehabilitation services, referrals were only linked to impairment-related concerns of mobility, lymphedema management, debility, and swallowing.…”
Section: Discussionmentioning
confidence: 95%
“…There have been multiple calls-to-action to better understand the nature and magnitude of disability in cancer populations (Alfano and Pergolotti, 2018; Newman et al., 2019b). The World Health Organization’s International Classification of Functioning, Disability, and Health describes disability as a multifactorial construct among body structures and function, activities and participation, and contextual factors (World Health Organization, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intentionally looking into the personal experiences of individuals diagnosed with cancer adds value to the body of literature. Newman et al. (2019) identified that the construct of participation involves a deeper understanding of various factors including cultural expectations.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a call to action for the promotion of strategies that facilitate return to work, school, and life for survivors of cancer [19]. However, evaluating participation in life activities in individuals with cancer is an underdeveloped component of cancer rehabilitation programs [20]. With the push to integrate this concept into the continuum of cancer care [20], understanding how participation is currently measured in this population is essential.…”
Section: The World Health Organization (Who) Developed the Internatiomentioning
confidence: 99%